Women, schooling, and marriage in rural Philippines - Sanjaya DeSilva; Mohammed Mehrab Bin Bakhtiar (Levy Economics Institute of Bard College, 2011)
Using data from the Bicol region of the Phillipines, we examine why women are more educated than men in a rural, agricultural economy in which women are significantly less likely than men to participate in the labor market. We hypothesize that educational homogamy in the marriage market and cross-productivity effects in the household allow Filipino women to reap substantial benefits from schooling regardless of whether they enter the labor market. Our estimates reveal that the return to schooling for women is approximately 20 percent in both labor and marriage markets. In comparison, men experience a 12 percent return to schooling in the labor market. By using birth order, sibship size, percent of male siblings, and parental education as instruments, we correct for a significant downward bias that is caused by the endogeneity of schooling attainment.
Keywords: I21; J12; J16; J24; O15; 330; returns to education; gender; marriage; Philippines